Applications of X-Chromosome Short Tandem Repeats for Human Identification: A Review: Applications of X-Chromosome Short Tandem Repeats for Human Identification - Naji Arafat Mahat; Aedrianee Reeza Alwi; Faezah Mohd Salleh; Seri Mirianti Ishar; Mohammad Rahim Kamaluddin; Mohd Radzniwan A. Rashid (Journal of Tropical Life Science, 2023)
The forensic DNA profiling technique has tremendously contributed to forensic human identification, an important aspect in forensic investigations. In instances whereby comparison samples are unavailable, utilization of short tandem repeats of X chromosome (X-STRs) may prove useful to resolve complex kinship investigations involving missing persons and mass disasters. Despite such evidential values, the use of X-STRs during investigations remains scarce in many Southeast Asian countries including Malaysia, requiring concerted efforts for establishing forensic statistical support for its diverse populations (especially the admixture populations), standardizing core loci and procedure, improving the knowledge among practitioners as well as developing suitable standard operating procedure for incorporating X-STRs analysis in the overall DNA profiling framework. Hence, this review paper aims to highlight the developments, applications and population data of X-STRs, as well as its challenges and future insights for forensic casework.